2011
DOI: 10.4103/0019-5154.80410
|View full text |Cite
|
Sign up to set email alerts
|

Comparative therapeutic evaluation of different topicals and narrow band ultraviolet B therapy combined with systemic methotrexate in the treatment of palmoplantar psoriasis

Abstract: Background:The incidence of uncomplicated psoriasis is 1–3% in the general population. The involvement of palm and sole is seen in 7–14.5% of cases. There are different topicals and systemic therapies available for treating the case of psoriasis but none is satisfactory for longer duration.Aim:The study involved the comparative therapeutic evaluation of the different topical regimens and narrow band ultraviolet B (NB-UVB) therapy in combination with systemic methotrexate.Materials and Methods:The study was hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Similar pattern of triple therapy has been reported in several other studies, but considered only for those cases with baseline PASI score >10. 6,[16][17][18]21,22 In GC monotherapy used as clobetasol, halobetasol and betamethsone (n=66), the decrease in the mean baseline score was 91.03%, which was highly significant (p<0.001). In patients treated with GC + SA (n=15), the decrease after 12 weeks of therapy was 82.73%.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Similar pattern of triple therapy has been reported in several other studies, but considered only for those cases with baseline PASI score >10. 6,[16][17][18]21,22 In GC monotherapy used as clobetasol, halobetasol and betamethsone (n=66), the decrease in the mean baseline score was 91.03%, which was highly significant (p<0.001). In patients treated with GC + SA (n=15), the decrease after 12 weeks of therapy was 82.73%.…”
mentioning
confidence: 99%
“…The baseline PASI score recorded was in accordance with other studies, which have also observed that majority of the patients had less severe lesions with PASI <10. [6][7][8][9]11,16,17 Most of the patients (n=95; 78.51%) were treated with topical medications, which included GC, SA, calcitriol and coal tar, either as monotherapy or in combination of two or more drugs, in the form of creams or ointments. Clobetasol and halobetasol are the most potent topical steroids preferred in psoriasis for their anti-inflammatory and antiproliferative action.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to a systematic review by Li l et al 16 current topical treatments including laser therapy, tazarotene ointment and methotrexate gel apart from phototherapy do not have sufficient evidence to justify their use. None theless, phototherapy needs to be administered over a long treatment period, around 21.9 months before noticeable improvements can be seen, 17 it also causes erythema, irritation and burning. 16,17,18 Topical methotrexate has been advocated as an adequate alternative to systemic side effects with less adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…None theless, phototherapy needs to be administered over a long treatment period, around 21.9 months before noticeable improvements can be seen, 17 it also causes erythema, irritation and burning. 16,17,18 Topical methotrexate has been advocated as an adequate alternative to systemic side effects with less adverse effects. 19 However, a small prospective, open label study involving fourteen patients showed variable results by Kumar et al 20 Similar to PUVA various side effects have been reported with topical methotrexate including redness, burning sensation, purpura and blisters at the site of application.…”
Section: Discussionmentioning
confidence: 99%